2021
DOI: 10.1017/s0007114521000738
|View full text |Cite
|
Sign up to set email alerts
|

Zinc deficiency as a possible risk factor for increased susceptibility and severe progression of Corona Virus Disease 19

Abstract: The importance of zinc for human health becomes obvious during zinc deficiency. Even mild insufficiencies of zinc cause alterations in haematopoiesis and immune functions, resulting in a pro-inflammatory phenotype and a disturbed redox metabolism. Although immune system malfunction is the most obvious effect, the functions of several tissue cell types are disturbed if zinc supply is limiting. Adhesion molecules and tight junction proteins decrease while cell death increases, generating barrier dysfunction and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 263 publications
2
32
1
Order By: Relevance
“…Additionally, as mentioned in a recently published review study, zinc may have beneficial effects including a decreased susceptibility to infection in the current and future pandemics [51]. In contrast to our study results, a review study revealed that a pre-existing severe zinc deficiency predisposes patients to a stronger progression of SARS-CoV-2 infections, and even a mild zinc deficiency should be corrected to prevent a more severe viral infection [5]. However, in the present study, no significant difference was observed between the serum concentration of zinc and the severity of COVID-19 disease, which may be due to insufficient sample size.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…Additionally, as mentioned in a recently published review study, zinc may have beneficial effects including a decreased susceptibility to infection in the current and future pandemics [51]. In contrast to our study results, a review study revealed that a pre-existing severe zinc deficiency predisposes patients to a stronger progression of SARS-CoV-2 infections, and even a mild zinc deficiency should be corrected to prevent a more severe viral infection [5]. However, in the present study, no significant difference was observed between the serum concentration of zinc and the severity of COVID-19 disease, which may be due to insufficient sample size.…”
Section: Discussioncontrasting
confidence: 90%
“…While therapeutic options are still under investigation, and some vaccines have been approved, cost-effective ways to reduce the probability of or even prevent infection and the shift from mild symptoms to more serious detrimental disease are highly worthwhile [5].…”
Section: Introductionmentioning
confidence: 99%
“…This effect is zinc dependent and allicin increases [Zn 2+ ]cyt by causing intracellular Zn 2+ release from proteins by oxidizing the Cys residues which chelate it, e.g., from SOD-1, shown to be a major target for S-thioallylation in human Jurkat cells [90]. The importance of Zn 2+ for the immune system in relation to preventing severe COVID-19 has recently been reviewed [101].…”
Section: Allicin Activity Against Respiratory Tract Pathogensmentioning
confidence: 99%
“…The antiviral property of zinc has been studied extensively, including coronavirus, hepatitis C virus, and HIV infections [70,71]. Pre-existing zinc deficiency may pre-dispose patients to a severe progression of COVID-19 [72,73]. Zinc supplementation may reduce the incidence of acute lower respiratory infection [74].…”
Section: Zincmentioning
confidence: 99%